2010
DOI: 10.1088/0953-8984/22/45/454133
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that small proteins translocate through silicon nitride pores in a folded conformation

Abstract: The interaction of three proteins (histidine-containing phosphocarrier protein, HPr, calmodulin, CaM, and maltose binding protein, MBP) with synthetic silicon nitride (SiN(x)) membranes has been studied. The proteins which have a net negative charge were electrophoretically driven into pores of 7 and 5 nm diameter with a nominal length of 15 nm. The % blockade current and event duration were measured at three different voltages. For a translocation event it was expected that the % block would be constant with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…A likely explanation for the observed voltage dependences, as previously reported in the literature for other moleules, [42][43][44][45][46] is that at potentials lower than the dwell time maximum (−40 mV for Type I ClyA-AS and −30 mV for Type II ClyA-CS) the majority of DHFR ST proteins enter and exit the nanopore from the cis side, while at potentials above the dwell time maximum the majority of proteins translocate through the nanopore (Figure 2c,d). (Figure 3b,c, step 3, Figure S4b, Figure S5).…”
Section: Resultssupporting
confidence: 74%
“…A likely explanation for the observed voltage dependences, as previously reported in the literature for other moleules, [42][43][44][45][46] is that at potentials lower than the dwell time maximum (−40 mV for Type I ClyA-AS and −30 mV for Type II ClyA-CS) the majority of DHFR ST proteins enter and exit the nanopore from the cis side, while at potentials above the dwell time maximum the majority of proteins translocate through the nanopore (Figure 2c,d). (Figure 3b,c, step 3, Figure S4b, Figure S5).…”
Section: Resultssupporting
confidence: 74%
“…4, panels c and d). The indirect indication relating analyte translocation by its voltage-dependence dissociation from the nanopore, as used above, was also described and discussed for the case of other analytes 5055 . Note that for the larger PAMAM-G2 dendrimer, at both pH’s, an increase in the applied potential led to an increase of the dendrimer’s dissociation time (τ off ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experiments have shown that folded proteins give smaller blockade currents than the corresponding random coil but it is not clear that different conformations would yield different signatures since the occluded volumes would be very similar. 70 There are also problems with the reproducibility of solid state pores since it is very difficult to control the diameter during fabrication and the chemistry of the internal surfaces can be quite variable. One elegant solution is to coat the pore with a lipid.…”
Section: Protein Misfoldingmentioning
confidence: 99%